The Impact Study of Flexible Alternating Current Transmission System on Transient Stability of Power Systems Using MATLAB CODE and Power World Simulator - ELBAR Mohamed; Abdelhafid Hellal; Aissa Souli; Redha Djamel Mohammedi (ITEGAM-JETIA)
The purpose of this work is the study of the influence of FACTS on transient stability of power systems using a Power World Simulator software, and the computer code transient stability code 'TRANS_STAB_CODE' 'which was created in MATLAB. We tried in the introduction of this work to provide a description on the transient stability: definition, transient stability criteria, and equations. Then we gave an overview on the modelling of FACTS in power systems, the definition and types of Flexible Alternating Current Transmission System, their schemes, and their equations, then presented the model of UPFC (Unified Power Flow Controller) as an example. Secondly, we discussed the code, 'TRANS_STAB_CODE' that was created in MATLAB by giving a description of the code and their structure with graphics windows, and then I described privately the Power World